New Lessons in Hypertension and Diabetes: An Update on Clinical Trials and Clinical Guidelines - Vinall, Phil (MD Conference Express, 2012)
This article revisits the 2003 JNC 7 guidelines, as well as newer evidence regarding the use of renin-angiotensin system (RAS) inhibitors, calcium channel blockers, and diuretics to treat patients with diabetes and hypertension. The American Diabetes Association issued new guidelines in 2012 to address some of the recent controversy concerning the use of antihypertensive agents in patients with diabetes and to provide additional recommendations concerning the use of RAS inhibitors. These recommendations were based on evidence from a number of clinical trials.